2021
DOI: 10.1097/01.ogx.0000751592.86339.dc
|View full text |Cite
|
Sign up to set email alerts
|

The World Ovarian Cancer Coalition Every Woman Study: Identifying Challenges and Opportunities to Improve Survival and Quality of Life

Abstract: The prognosis for ovarian cancer remains poor even in highly developed countries such as the United States, with approximately 1 in 6 women dying within 3 months of diagnosis and 1 in 2 dying within 5 years. Given that the global incidence of ovarian cancer is set to rise 55% by 2035, urgent action is required to improve survival and quality of life in this patient population. The World Ovarian Cancer Coalition (the coalition) is a not-for-profit organization comprising 135 patient advocacy group members in 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…According to one study, 69% of women with OvCa had never heard of it or knew nothing about it before their diagnosis, and only about 20% of women with OvCa believed they had received all of the information they required at any point. 2 Moreover, about half of those women reported that their doctor spent <15 min informing and discussing their diagnosis of OvCa. 2 …”
Section: Background and Significancementioning
confidence: 99%
See 1 more Smart Citation
“…According to one study, 69% of women with OvCa had never heard of it or knew nothing about it before their diagnosis, and only about 20% of women with OvCa believed they had received all of the information they required at any point. 2 Moreover, about half of those women reported that their doctor spent <15 min informing and discussing their diagnosis of OvCa. 2 …”
Section: Background and Significancementioning
confidence: 99%
“… 2 Moreover, about half of those women reported that their doctor spent <15 min informing and discussing their diagnosis of OvCa. 2 …”
Section: Background and Significancementioning
confidence: 99%